Background and ways to implement BIM concept in the construction industry - Tugay, A. A.; Pokolenko, V. O.; Yesipenko, A. D.; Dubinka, A. V. (Ways to Improve Construction Efficiency, 2020)
The article is aimed at considering the content of information modeling of construction and investment projects through the joint application of BIM-technologies (Building Information Modeling - information modeling of buildings) for the full life cycle of construction objects. The use of this approach in the implementation of investment and construction projects makes it possible to detail the project in order to make timely decisions at every stage of the project life cycle, from the concept of a future facility to its operation. Building information modeling technologies make it possible to determine and increase the level of interaction between project participants and improve the organization of collaboration between all construction participants. This requires quantitative and qualitative transformations, including the transition to information modeling and in areas related to construction, which contribute to a more efficient allocation of investments and the formation of the optimal project cost, solving the problems of increasing construction volumes and implementing large-scale infrastructure projects in optimal terms at the state level. Determining the prerequisites and ways of implementing the BIM concept with the optimization of business processes is relevant and requires scientific substantiation and implementation of the study of information modeling technology in the educational process for a high-quality and professional approach to construction projects in practice.